Traffic architecture motivated Learning Object organisation in a virtual environment. (14th January 2008) - Mahfujur Rahman, A.S.M.; El Saddik, Abdulmotaleb
This paper introduces a structuring method applied to a collection of searched Learning Objects (LOs). Firstly, frequencies of the search keywords are calculated. Then the LOs are grouped under the most ranked keywords. The ranked keywords are taken further into consideration for finding semantic relation metrics that allow us to present the groups visually; for which we have adopted a 3D highway metaphor where these groups are positioned along the dynamically constructed road segments. Since the groups are inter-connected using road networks in accordance to the relation metrics, it leverages the navigational experience of a user while searching for the topic of interest.